Effects of Three-Layer Encapsulated Tea Tree Oil on Growth Performance, Antioxidant Capacity, and Intestinal Microbiota of Weaned Pigs - Wang, Lixue; Zhang, Ying; Liu, Ling; Huang, Fei; Dong, Bing (Frontiers in Veterinary Science, 2021)
Tea tree oil (TTO) exerts key roles in improving growth performance of pigs. However, knowledge is limited regarding comparative effects of encp TTO and un-encp TTO supplementation on growth performance of pigs. A study determined the effects of TTO or its capsulation on growth performance, antioxidant capacity and intestinal microbiome of weaned pigs. A total of 144 healthy pigs (8.5 ± 0.24 kg) were subjected to four treatments for a 28 d trial with six replicates per treatment and six pigs per pen: Negative control, NC; Positive control, PC (antibiotic supplemented); Un-encp TTO (supplemented with un-encapsulated TTO); Encp TTO (supplemented with encapsulated TTO). Comparing to NC, TTO and PC treatments improved average daily gain (ADG), average daily feed intake (ADFI), feed conversion rate, nutrient digestibility, intestinal morphology (P < 0.05) and decreased diarrhea rate. TTO and PC treated pigs had higher levels of serum superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and immunoglobulins G (IgG); lower levels of liver aminotransferase (AST) and alanine aminotransferase (ALT); and improved concentrations of interleukin-10 (IL-10), tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β, P < 0.05). TTO and PC treated pigs had higher abundance of beneficial bacterial species Subdoligranulum and lower abundance of diarrhea associated species Escherichia-Shigella in cecal and colonic digesta (P < 0.05). Encapsulation of TTO preserved more activities of TTO than its un-encapsulated counterpart by showing higher ADG, ADFI, feed conversion rate during d1 to d14 (P < 0.05), and tended to lower diarrhea rate (P = 0.083) and improve villous height/crypt depth (VH/CD) ratio (P = 0.089) in jejunum. Encapsulation of TTO also improved antioxidant indexes and decrease liver injury and inflammatory accordingly (P < 0.05). Encapsulated TTO treated pigs had higher abundance of beneficial Clostridium_sensu_stricto_1 and lower the abundance of harmful Escherichia-Shigella in cecal and colonic digesta (P < 0.05). Our results demonstrated TTO benefits on improving growth performance of weaned pigs and further proved encapsulation of TTO was superior to its un-encapsulated counterpart at multiple. Encapsulated TTO was similar to the PC group and could be potentially an alternative of feed antibiotics for weaned pigs.